1990
DOI: 10.1182/blood.v75.4.851.bloodjournal754851
|View full text |Cite
|
Sign up to set email alerts
|

Human granulocyte colony-stimulating factor: biologic activities and receptor characterization on hematopoietic cells and small cell lung cancer cell lines

Abstract: Human granulocyte colony-stimulating factor (G-CSF) is a regulatory glycoprotein that stimulates the production of neutrophilic granulocytes from committed hematopoietic progenitor cells both in vitro and in vivo. In this report, we show that biosynthetic (recombinant) human G-CSF enhances colony formation by normal human bone marrow and the human myeloid leukemic cell lines, HL-60 and KG-1, as well as nonhematopoietic small cell lung cancer lines, H128 and H69. G-CSF also modulates multiple differentiated fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
4

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 0 publications
2
54
0
4
Order By: Relevance
“…The estimated K D value is close to a value of 90.8 pM obtained by us from the in vitro Biacore-based binding assay (data not shown), and in the range of 70 to 150 pM reported elsewhere. 23,29 The estimated Ο value is larger than the number of G-CSF receptors per neutrophil, 50 to 500 reported in the literature. 1 This large value could account for nonspecific binding or underestimation of neutrophils in the bone marrow.…”
Section: Resultsmentioning
confidence: 54%
“…The estimated K D value is close to a value of 90.8 pM obtained by us from the in vitro Biacore-based binding assay (data not shown), and in the range of 70 to 150 pM reported elsewhere. 23,29 The estimated Ο value is larger than the number of G-CSF receptors per neutrophil, 50 to 500 reported in the literature. 1 This large value could account for nonspecific binding or underestimation of neutrophils in the bone marrow.…”
Section: Resultsmentioning
confidence: 54%
“…Vellenga et al (1987) reported that rhG-CSF stimulates the proliferation of human myeloid leukemia cells in vitro. Avalos et al (1990) showed that rhG-CSF stimulates the in vitro proliferation of non-hematopoietic small-cell lung-cancer cells that possess receptors for G-CSF on the cell surface. , however, reported that although rhG-CSF stimulates in witro proliferation of mouse leukemic cells, it inhibits the development of leukemic cells in vivo.…”
Section: Cytostasis To Tumor Cells By Neutrophils From Mice Injected mentioning
confidence: 99%
“…A specific role for LRG in granulopoiesis has not been elucidated. G-CSF has been shown to be the major regulator of granulopoiesis [4] and supports not only the survival, proliferation, and neutrophilic differentiation of myeloid progenitor cells but also activates certain functions of mature, terminally differentiated neutrophils [5][6][7]. The biological activities of G-CSF are mediated by specific receptors on the surface of responsive cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice with knockout or knock-in mutations in the G-CSFR gene suggest that the G-CSFR generates unique, nonredundant signals required for polymorphonuclear neutrophil (PMN) production and marrow egress to maintain homeostatic levels of circulating PMN [7][8][9][10]. G-CSFR knockout mice have chronic neutropenia with a uniform decrease in myeloid cells in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%